Sorption/desorption of phenanthrene and ofloxacin by microbial-derived organic matter-mineral composites - Li, Fangfang; Yan, Qiuling; Li, Zhongwen; Tan, Zhicheng; Li, Yuxuan; Wang, Siyao; Guo, Jiawen; Peng, Hongbo; Wang, Lin (Frontiers in Environmental Science, 2024)
Soil organic matter plays an important role in the long-term "locking" of organic contaminants in soil environment. Recently, microbial-derived organic matter have been recognized as essential components of stabilized soil carbon pools. However, the contribution of microbial-derived organic matter to sorption of organic contaminants remains unclear. Here, we obtained microbial-derived organic matter-mineral composites by inoculating model soil (a mixture of hematite and quartz sand (FQ) or montmorillonite and quartz sand (MQ)) with natural soil microorganisms and different substrate-carbon (glycine (G), glucose (P), or 2, 6-Dimethoxyphenol (B)), which were named GF, PF, BF, GM, BM, and PM, respectively. Batch sorption/desorption experiments were conducted for phenanthrene (PHE) and ofloxacin (OFL) on the composites. The composites cultured with 2,6dimethoxyphenol had the highest carbon content (0.98% on FQ and 2.11% on MQ) of the three carbon substrates. The carbon content of the composites incubated with MQ (0.64%-2.11%) was higher than that with FQ (0.24%-0.98%), indicating that montmorillonite facilitated the accumulation of microbialderived organic matter owing to its large specific surface area. The sorption of PHE by microbialderived organic matter was mainly dominated by hydrophobic partitioning and π-π conjugation, whereas the sorption of OFL was mainly dominated by hydrophobic hydrogen bonding and π-π conjugation. The sorption of OFL onto the composites was more stable than that of PHE. Microbialderived organic matter -mineral composites can reduce the risk of organic contaminant migration in soil, particularly ionic organic contaminants.